Does a taller husband make his wife happier?. (March 2016) - Sohn, Kitae
Abstract: Although it has been known that women prefer tall men in mating for evolutionary reasons, no study has investigated whether a taller husband makes his wife happier. We analyzed two datasets (N = 7850) that are, together, representative of the Indonesian population to determine whether this is true. A greater height difference in a couple was positively related to the wife's happiness. This relationship gradually weakened over time and entirely dissipated by 18 years of marital duration. The husband's resourcefulness was a minor mediator in the relationship. We thus argue that the husband's height and its correlates made his wife initially happy, but their influence waned over time. Nevertheless, the long period of the dissipation indicates a powerful impact of male height on women's psychology, probably prepared by evolution. Highlights: We investigated whether women are happier with taller husbands. We employed nationally representative Indonesian data. A greater height difference in a couple was positively related to the wife's happiness. This relationship entirely dissipated by 18 years of marital duration. The long period of dissipation indicates a strong impact of male height on women.